Análisis del capital humano de los productores agroecológicos de la provincia de Tungurahua, Cotopaxi 2021-2022. - Mendoza Laglaguano, Gabriela Lizeth (2022)
The purpose of this research is to study the analysis of the human capital of the PACAT association in times of pandemic COVID-19 coronavirus disease, which directly affected the world economy, creating disruptions in the supply chain and the market. Emphasizing the research, we started by recognizing the place and the proper zoning in different cantons: Pelileo, Píllaro, Ambato, Quero, and Tisaleo. Therefore, we established a study technique such as the survey using a digital form (Google Forms). Based on human indicators (effective training, knowledge about efficient and environmentally friendly technologies, education, and food security and sovereignty - nutrition), allowing us to know the current reality of each producer of the different associations, the same was given with the participation of 140 producers as respondents. Applying statistical methods such as simple statistical analysis and multivariate analysis (principal component analysis, cluster analysis, and radial graphs) allowed us to identify the critical points that exist in human capital. The result was an overall average value of 0.06 regarding the criteria considered to be able to produce. Therefore, it is considered the most critical point of the research. It was determined that the producers' lack of knowledge, skills, abilities, skills, attitudes, and capacities could lead to the lack of profitability in the production and commercialization of their products.